2022
DOI: 10.1002/jsfa.12141
|View full text |Cite
|
Sign up to set email alerts
|

Research on apoptotic mechanism and related pathways involved in postmortem grass carp (Ctenopharyngodon idellus) muscle

Abstract: BACKGROUND Apoptosis activation is an essential research to reveal the triggering mechanism of flesh quality deterioration. This study was aimed at explaining apoptotic mechanism of postmortem fish in terms of caspases activation, cytochrome c (cyt‐c) release, B‐cell lymphoma 2 (Bcl‐2) and Bcl2‐associated X (Bax) protein levels, transcriptional levels of its molecules, and apoptosis‐inducing factor (AIF) translocation at 4 °C for 5 days. RESULTS Activation of caspase‐9, caspase‐8, caspase‐3 and the release of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…When apoptosis occurs, the ratio of Bax to Bcl-2 increases, resulting in the release of Cyt C from mitochondria. This activates the release of caspase-3 and caspase-9 and then induces apoptosis [60]. In the present study, expression levels of Bax and Bcl-2b were inhibited by metamifop, but the ratio of Bax to Bcl-2b increased.…”
Section: Discussionsupporting
confidence: 46%
“…When apoptosis occurs, the ratio of Bax to Bcl-2 increases, resulting in the release of Cyt C from mitochondria. This activates the release of caspase-3 and caspase-9 and then induces apoptosis [60]. In the present study, expression levels of Bax and Bcl-2b were inhibited by metamifop, but the ratio of Bax to Bcl-2b increased.…”
Section: Discussionsupporting
confidence: 46%
“…44 Cyt C is a pro-apoptotic factor that binds with apoptotic protease activating factor-1 (APAF-1) to activate pro-caspase-9. 45 Caspase-3 is involved in a cascade of reactions that ultimately lead to apoptosis. The PI3K-AKT signaling pathway regulates tumor cell proliferation and resistance to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The changes of tenderness in muscle is a very complex process, which was altered by numerous factors including endogenous enzymes, oxidation and apoptosis process. 42 Previous study emphasized the importance of collagen involved in texture softening, and the decrease of collagen was tightly associated with the decline of texture. 43 The content of hydroxyproline was widely used to evaluate the amount of collagen.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that dietary MOS decreased shear force, indicating that MOS in fish diet could enhance tenderness (27.4%) in fish muscle. The changes of tenderness in muscle is a very complex process, which was altered by numerous factors including endogenous enzymes, oxidation and apoptosis process 42 . Previous study emphasized the importance of collagen involved in texture softening, and the decrease of collagen was tightly associated with the decline of texture 43 .…”
Section: Discussionmentioning
confidence: 99%